2012
DOI: 10.3892/or.2012.1865
|View full text |Cite
|
Sign up to set email alerts
|

Klotho inhibits the capacity of cell migration and invasion in cervical cancer

Abstract: Abstract. Aberrant activation of the Wnt/β-catenin signaling pathway is common in human cervical cancers. However, the mechanisms of Wnt activation in cervical cancer remain largely unknown. In the present study, we demonstrate that Klotho, a Wnt antagonist, is downregulated in invasive human cervical tumors and in a cell line we analyzed. Our data demonstrated that in vivo Klotho expression was not observed in invasive cervical carcinoma. In vitro restoration of Klotho expression in SiHa cells resulted in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 37 publications
1
50
1
1
Order By: Relevance
“…Some reports have shown a reduction in the expression of Klotho in invasive breast cancers or cervical cancers, compared with normal lesions (19,20). Moreover, the expression of Klotho has been observed in carcinoma in situ, but not in invasive carcinoma (20,21). As shown in Figs.…”
Section: Discussionmentioning
confidence: 71%
“…Some reports have shown a reduction in the expression of Klotho in invasive breast cancers or cervical cancers, compared with normal lesions (19,20). Moreover, the expression of Klotho has been observed in carcinoma in situ, but not in invasive carcinoma (20,21). As shown in Figs.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies have established a strong link between high levels of EMT transcription factors and increased cancer cell metastasis (26,27). SNAI2 is overexpressed in numerous cancers and also promotes invasion in lung adenocarcinoma, glioma, ovarian, cervical, and pancreatic cancers and is a prognostic marker in some cancers (7,28,29). A recent study found overexpression of SNAI2 in aggressive thyroid cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…KL has also been implicated as a tumor-suppressor protein in numerous cancers (Camilli 2010;Chang et al 2012;Chen 2010;Lee 2010;Wang 2011;Wolf 2008) where decreased expression promotes tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%